Erratum to: The sports-related injuries and illnesses in paralympic sport study (SRIIPSS): a study protocol for a prospective longitudinal study - Fagher, K.; Jacobsson, J.; Timpka, T.; Dahlström, Ö.; Lexell, J. (BMC Sports Science, Medicine and Rehabilitation, 2016)
After publication of the original article [1], it came to the authors` attention that there was a formatting error within Table 1 which reduced the legibility of the content. In row 1 of the `Impairments` column, "Impaired muscle power" and "Impaired passive range of movement" appear on the same line, as opposed to split over two lines within the same cell. This has been corrected in the original article and the correct version of Table 1 is published here.